IMPACTS OF SCAFFOLDING ON LEARNER AUTONOMY – A CASE STUDY IN AN INTERCULTURAL COMMUNICATION COURSE (Journal of Foreign Language Studies, 2025)
This case study investigates the impacts of scaffolding on the development of learner autonomy in an Intercultural Communication course at the English Department of Hanoi University, Vietnam. Data were collected through semi-structured interviews with eleven student participants. The findings indicate that scaffolding significantly enhances learner autonomy by gradually shifting responsibility from instructors to students. The strategic application of scaffolding throughout and beyond the course enabled students to exhibit behaviors characteristic of progressively higher autonomy. This study highlights the essential role of scaffolding in fostering learner autonomy and emphasizes the need for educators to integrate structured scaffolding strategies into language courses.
Keywords: scaffolding; learner autonomy; development